Scientific production on the Marajoara Wrestling in Brazil: an integrative review study and state of art analysis - Lima, George Almeida; Pereira, Marcos Paulo Vaz de Campos; Rufino, Luiz Gustavo Bonatto [UNESP] (Editora Univ Leopoldlanum, 2023)
The aim of this investigation was to map and analyze the scientific production on Luta Marajoara (LM) in stricto sensu postgraduate programs in Brazil, as well as in scientific papers and event annals. Only one study published in 2021 was found in the catalog of theses and dissertations. Regarding the production of papers and annals, 16 studies were included. Studies on LM are inci- pient and recent, starting in 2018. Although the Northern region of Brazil is the place of origin of LM, no postgraduate studies have come from this region. The studies found in the literature present discussions focused on the educational, sports, cultural, traditional, health and teacher education fields. It is concluded that more studies on LM are needed in Brazil, given its social relevance and its understanding as a bodily practice strongly linked to Brazilian culture.
Keywords: Marajoara Wrestling; Body Practices; Physical Education; Academic production; State of Art